2019
DOI: 10.1093/jisesa/iey122
|View full text |Cite
|
Sign up to set email alerts
|

Improvements in the Rearing of the Tachinid ParasitoidExorista larvarum(Diptera: Tachinidae): Influence of Adult Food on Female Longevity and Reproduction Capacity

Abstract: Exorista larvarum (L.), a polyphagous gregarious larval parasitoid of lepidopterans, can be mass produced both in vivo, using the greater wax moth Galleria mellonella (L.) (Lepidoptera: Pyralidae) as a factitious host, and in vitro, on artificial media composed of crude components. The present study was focused on another aspect of E. larvarum rearing, namely the influence of adult food on parasitoid performance. The standard food, consisting of lump suc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 40 publications
0
10
0
Order By: Relevance
“…The tachinid fly E. japonica was collected on its host, the M. separata in the field in Nanning, Guangxi, China. The rearing of E. japonica was followed by the method developed for the tachinid parasitoid Exorista larvarum (Diptera: Tachinidae) ( Dindo et al, 2019 ). Briefly, newly emerged adults were fed with 20% honey solution; after mating, each of the fly cages was loaded with 100 silkworm larvae on day 1 at the last (fifth) instar for receiving fly eggs.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The tachinid fly E. japonica was collected on its host, the M. separata in the field in Nanning, Guangxi, China. The rearing of E. japonica was followed by the method developed for the tachinid parasitoid Exorista larvarum (Diptera: Tachinidae) ( Dindo et al, 2019 ). Briefly, newly emerged adults were fed with 20% honey solution; after mating, each of the fly cages was loaded with 100 silkworm larvae on day 1 at the last (fifth) instar for receiving fly eggs.…”
Section: Methodsmentioning
confidence: 99%
“…Around 120 silkworms (sex ratio F/M = 1:1) on day 1 in the fifth instar stage were placed in the adult fly cages to receive fly eggs for 2 h. Due to 64% parasitoidism success in silkworms, silkworms received 2–3 fly eggs were selected and reared with mulberry leaves for further observation ( Zhao et al, 2020 ). The newly hatched tachinid larvae penetrated the host body and each formed a visible black-marked respiratory funnel on the silkworm integument ( Dindo et al, 2019 ). The number of silkworms with one and two funnels, the emerged tachinid puparia, and adults were recorded.…”
Section: Methodsmentioning
confidence: 99%
“…The parasitoid adults were kept in plexiglass cages (40 × 30 × 30 cm) (50–70 adults per cage) at 26 ± 1 °C, 65 ± 5% r.h., and L16:D8 photoperiod. Adult food consisted of sugar cubes and pollen (Dindo et al, 2019). Distilled water was administered via drinking troughs with soaked cotton.…”
Section: Methodsmentioning
confidence: 99%
“…In agreement with previous studies (Jalali & Singh, 1992;Silva et al, 2013;Ismail et al, 2014), our results demonstrated that the fecundity of A. matricariae decreased after cold storage. In addition, the nutritional status of parasitoids during their adult stage can affect fecundity (Heimpel et al, 1997;Dindo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%